Save the Whales! Using Marine Research in Math and Science Classrooms - Micki Halsey Randall (Current: The Journal of Marine Education, 2023)
During the 2019–2020 academic year, I participated in a yearlong professional development (PD) opportunity that resulted in a co-curricular unit developed in collaboration with a marine researcher, a math teacher, and a marine biology teacher. Together we created a unit of study for students to utilize authentic marine research data points. Using the 5E model of instruction and anchoring phenomena, we developed a sequence of learning events for students to connect biology concepts with current local context. In the fall of 2019, I implemented the learning unit we had created. The next school year, I adjusted the curriculum because of the global pandemic and subsequent distance learning. The 2021–2022 school year saw yet another revision and more synchronous learning in algebra and biology as students worked in both classes to develop their culminating project. In all three versions of our curriculum, students responded positively to the learning experiences. As an educator, I appreciated the opportunity to collaborate with other educators and learn from a marine researcher and found excitement in using authentic data in the classroom.